Pengaruh Pengungkapan Emisi Karbon, Biaya Lingkungan, dan Good Corporate Governance terhadap Nilai Perusahaan - Ida Ayu Kade Pradnyawati; Desak Nyoman Sri Werastuti (Universitas Pendidikan Ganesha, 2024)
This research aimed to determine the effect of disclosure of carbon emissions, environmental costs, and good corporate governance on company value. The grand theories used were the Signaling Theory and Regulation Theory. This type of research was quantitative, using multiple linear regression analysis. The research used secondary data originating from financial reports and movements, with a population of transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) for the period 2021 - 2022. The number of samples in this research was 16 companies. Samples were taken using a purposive sampling method based on certain criteria, namely obtaining positive profits and publishing sustainable reports during consecutive research years. Data processing was carried out with the help of the SPSS v.23 for Windows application. The research findings are as follows: (1) carbon emission disclosure negatively and insignificantly influences firm value, (2) environmental costs negatively and insignificantly influence firm value, and (3) good corporate governance positively and insignificantly influences firm value.